UPAYA PENINGKATAN KUALITAS PEMBELAJARAN AKUNTANSI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT(NUMBERED HEADS TOGETHER) KELAS XI IPS SMA NEGERI 3 SRAGEN TAHUN AJARAN 2012 / 2013 - atik, Mulyati; Martono, Trisno; M.Bus, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2014)
The Effort to Increase the Quality of the Learning Process of  Accounting through the Implementation of the Cooperative Learning Model of Numbered Heads Together (NHT) Type of the 11th-grade Students of SMA Negeri 3 Sragen Majoring in Social Science in the Academic Year of 2012/2013. Principal Advisor: Prof. Dr. Trisno Martono, M.M. Co-advisor: Dr. Susilaningsih, M. Bus. Thesis: The Graduate Program in Economics Education, Sebelas Maret University. Surakarta. 2013.            The objectives of this research are to investigate: (1) the implementation of the learning model of Numbered Heads Together (NHT) type in increasing the quality of the learning process of Accounting  of the 11th-grade students of Class Social Science 4 of SMA Negeri 3 Sragen in the academic year of 2012/2013; and (2) the implementation of the learning model of Numbered Heads Together (NHT) type in increasing the quality of the learning result of Accounting of the 11th-grade students of Class Social Science 4 of SMA Negeri 3 Sragen in the academic year of 2012/2013.            This research used classroom action research approach. The samples of this research consisted of the 11th-grade students of Class Social Science 4 of SMA Negeri 3 Sragen as many as 32 students. The data of this research were gathered through observation, interview, test, and documentation. The procedure of this research consisted of the stages of: (1) identifying problems, (2) preparing actions, (3) setting up action plan, (4) implementation of actions, (5) observation, and (6) setting up report. The process of this research was conducted in two cycles. Each cycle consisted of four stages, namely: (1) planning of action, (2) implementation of action, (3) observation and interpretation, and (4) analysis and reflection. Each cycle was conducted in three meetings as long as 6 x 45 minutes.            Based on the results of the research, a conclusion is drawn that the implementation of the learning model of Numbered Heads Together (NHT) type can increase the quality of the learning process and the learning result of Accounting. This is seen from the increasing learning activeness of the students in the apperception, in taking part of the learning process, in discussing the question exercise in class punctually and correctly as well as the learning result completeness. As a result, the students can comprehend the learning material of Accounting more easily in such a way that the quality of the learning process and the learning result of the students increases. The learning process through the learning model of Numbered Heads Together (NHT) type can increase the learning quality through the steps which have been established previously in the Lesson Plan. Thus, the implementation of the learning model of Numbered Heads Together (NHT) type increases the quality of the learning process and the learning result of the students.Keywords: learning motivation, learning participation, learning activeness, and completeness